Advances in accounting education. Vol. 19 teaching and curriculum innovations - Rupert, Timothy J.; Kern, Beth Burchfield, 1958- (Bingley, U.K. : Emerald, 2016)
Advances in Accounting Education: Teaching and Curriculum Innovations 19 publishes both non-empirical and empirical articles dealing with accounting pedagogy. All articles explain how teaching methods or curricula/programs can be improved. Non-empirical papers are academically rigorous, and specifically discuss the institutional context of a course or program, as well as any relevant tradeoffs or policy issues. Empirical reports exhibit sound research design and execution, and develop a thorough motivation and literature review, including references from outside the accounting field, where appropriate.
Tenure track opt-outs: leakages from the academic pipeline / Elizabeth Dreike Almer, Amelia A. Baldwin, Allison Jones-Farmer, Margaret Lightbody, Louise E. Single -- Debits, credits, and circadian rhythms: the effect of CPA exam start time on performance / Greg Gaynor, Susan A. Lynn, Olaf Wasternack -- Flipping the managerial accounting principles course: effects on student performance, evaluation, and attendance / Tom Downen, Becky Hyde -- Peer-to-peer implementation of an action-oriented ethics framework in the introductory accounting sequence / Jane Cote, Claire Latham -- Teaching inherent risk and tolerable misstatement in auditing: a modified delphi method as a teaching tool / Richard J. Barndt, Lori R. Fuller, Kevin E. Flynn -- Leveraging online testing to enhance student learning / Tommy Wooten -- Retail leases: a research exercise examining archived, current, and future standards / Natalie Churyk, Alan Reinstein, Lance Smith.
Includes bibliographical references.
Print version record
Keywords: Business & Economics -- Accounting -- General; Accounting; Finance & accounting; Accounting -- Study and teaching; Educational innovations